Pulmonary Interstitial Matrix and Lung Fluid Balance From Normal to the Acutely Injured Lung - Beretta, Egidio; Romanò, Francesco; Sancini, Giulio; Grotberg, James B.; Nieman, Gary F.; Miserocchi, Giuseppe (Frontiers in Physiology, 2021)
This review analyzes the mechanisms by which lung fluid balance is strictly controlled in the air-blood barrier (ABB). Relatively large trans-endothelial and trans-epithelial Starling pressure gradient result in minimal flows across the ABB thanks to low microvascular permeability aided by the macromolecular structure of the interstitial matrix. These edema safety factors are lost when the integrity of the interstitial matrix is damaged. The result is that small Starling pressure gradients, acting on a progressively expanding alveolar barrier with high permeability, generate high transvascular flows causing alveolar flooding in minutes. We modelled trans-endothelial and trans-epithelial Starling pressure gradients in control condition as well as on increasing alveolar pressure (Palv) up to 25cmH2O. We refer to the wet-to-dry weight (W/D) ratio, a specific index of lung water balance, to be correlated with the functional state of the interstitial structure. W/D averages 5 in control and might increase up to 9 in severe edema, corresponding to 70% loss of integrity of the native matrix. Factors buffering edemagenic conditions include: (i) an interstitial capacity for fluid accumulation located in the thick portion of ABB, (ii) the increase in interstitial pressure due to water binding by hyaluronan (the “safety factor” opposing the filtration gradient), and (iii) increased lymphatic flow. Inflammatory factors causing lung tissue damage include those of bacterial/viral and those of sterile nature. Production of reactive oxygen species (ROS) during hypoxia or hyperoxia or excessive parenchymal stress/strain (lung overdistension caused by Patient Self-Induced Lung Injury, P-SILI) can all cause excessive inflammation. We discuss the heterogeneity of intrapulmonary distribution of W/D ratios. A W/D 6.5 has been identified as being critical for the transition to severe edema formation. Increasing Palv for W/D>6.5, both trans-endothelial and trans-epithelial gradients favour filtration leading to alveolar flooding. Neither CT scan nor ultrasound can identify this initial level of lung fluid balance perturbation. A suggestion is put forward to identify a non-invasive tool to detect the earliest stages of perturbation of lung fluid balance before the condition becomes life threatening.